ELT teachers’ epistemological beliefs and dominant teaching style: a mixed method research - Neda Soleimani (Asian-Pacific Journal of Second and Foreign Language Education, 2020)
Abstract Despite voluminous studies into teachers’ cognition and the role of teachers’ beliefs in their practices, not many studies have addressed the impact of teachers’ epistemological beliefs (EB, beliefs about the source of knowledge) on their teaching styles. In this study, a mixed design research method was adopted to show English language teachers’ epistemological beliefs, teaching styles and possible relationships between EB and teaching styles. To do this, a sample of 200 EFL teachers participated in the quantitative phase of the study to fill out the teaching style inventory (Grasha, Teaching with style, 2002) and epistemological beliefs scale (Chan and Elliott, Teaching and Teacher Education 20:817–831, 2004). In qualitative phase, 20 participants of this sample volunteered to attend the semi-structured interviews. Both quantitative and qualitative analyses indicated that facilitator style is the dominant style of teaching and learners should not assume teachers as mere source of knowledge and should use different resources to learn the language. Regression analyses and interview results showed that EFL teachers teaching style is informed by their EB. Implication and limitation of the research were discussed in detail in the paper.